Analisis Balik Kestabilan Lereng Disposal di PIT Satelit Dengan Metode Bishop PT. Barasentosa Lestari di Desa Belani, Kabupaten Musi Rawas Utara, Provinsi Sumatera Selatan - Anita Sari Sundriya; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2023)
This study focuses on the slope of the disposal pit at Satellite PT Barasentosa Lestari, which experienced a landslide in March 2023. The landslide is a type of arc landslide and involves fractures and fill material such as mud. Therefore, a technical study was required, including a slope stability analysis of the design of the disposal area. The aim is to establish a basis for the establishment of the disposal area, prevent landslides, and optimize its capacity. This study aims to identify the slope stability of the disposal area, update the material properties of the area, provide slope design recommendations, and evaluate the slope safety factor at the study site. Bishop's method was used in this study. The results showed some important points. The slope geometry before the landslide had a total height of 82.152 meters, a slope inclination angle of 6°, and a slope length of 851.338 meters. The material properties of the existing wastedump include a specific gravity of 19 KN/m³, a cohesion of 45 KN/m², and an inner shear angle of 10°. The safety factor before the landslide with these parameters was 1.036. After re-analysis, the factor of safety value became 0.967 with the new material properties: specific gravity 19 KN/m³, cohesion 35 KN/m², and inner shear angle 10°. Slope geometry recommendations using Bishop's method resulted in a factor of safety of 1.394 with a single slope height of 10 meters and a slope angle of 35°. The width of the slope varied from RL -10 to RL 60, with lengths of 100m, 100m, 100m, 70m, 70m, 70m, 100m, and 262m respectively.Keywords: Kestabilan Lereng, Metode Bishop, Wastedump Existing, Faktor Keamanan, Analisis Balik.